The impact of pesticide suicide on the geographic distribution of suicide in Taiwan: a spatial analysis - Chang Shu-Sen; Lu Tsung-Hsueh; Sterne Jonathan AC; Eddleston Michael; Lin Jin-Jia; Gunnell David (BMC, 2012)
Abstract Background Pesticide self-poisoning is the most commonly used suicide method worldwide, but few studies have investigated the national epidemiology of pesticide suicide in countries where it is a major public health problem. This study aims to investigate geographic variations in pesticide suicide and their impact on the spatial distribution of suicide in Taiwan. Methods Smoothed standardized mortality ratios for pesticide suicide (2002-2009) were mapped across Taiwan's 358 districts (median population aged 15 or above = 27 000), and their associations with the size of agricultural workforce were investigated using Bayesian hierarchical models. Results In 2002-2009 pesticide poisoning was the third most common suicide method in Taiwan, accounting for 13.6% (4913/36 110) of all suicides. Rates were higher in agricultural East and Central Taiwan and lower in major cities. Almost half (47%) of all pesticide suicides occurred in areas where only 13% of Taiwan's population lived. The geographic distribution of overall suicides was more similar to that of pesticide suicides than non-pesticide suicides. Rural-urban differences in suicide were mostly due to pesticide suicide. Areas where a higher proportion of people worked in agriculture showed higher pesticide suicide rates (adjusted rate ratio [ARR] per standard deviation increase in the proportion of agricultural workers = 1.58, 95% Credible Interval [CrI] 1.44-1.74) and overall suicide rates (ARR = 1.06, 95% CrI 1.03-1.10) but lower non-pesticide suicide rates (ARR = 0.91, 95% CrI 0.87-0.95). Conclusion Easy access to pesticides appears to influence the geographic distribution of suicide in Taiwan, highlighting the potential benefits of targeted prevention strategies such as restricting access to highly toxic pesticides.